On the aggregation of bovine serum albumin - Madeira, Pedro P. (2024)
In an attempt to elucidate the aggregation behaviour of bovine serum albumin and its modulation by salt ions, size-exclusion high-performance liquid chromatography was used and complemented by dynamic light scattering. The influence of the protein concentration, and type and concentration of inorganic salt on the aggregation of albumin in solution have been analyzed. Based on the observations herein reported an aggregation mechanism is proposed, according to which (i) some functional groups of albumin dissociate in solution forming macromolecular ions; (ii) the macromolecular ions bind with each other into large aggregates; and (iii) the salt ions establish chemical equilibria with the charges of opposing character present in the macromolecular ions’ backbone, promoting or preventing the aggregation. The present work shows that the aggregation behaviour of bovine serum albumin in solution and its modulation by salt ions can be explained by chemical concepts, with chemical equilibrium playing an essential role.